Ambarticus myanmaricus gen. et sp. nov., the first diving beetle from mid-Cretaceous amber of northern Myanmar (Coleoptera, Dytiscidae, Dytiscinae). (October 2019) - Yang, Qiang; Chen, Zhao-Yang; Jia, Feng-Long
Abstract: Ambarticus myanmaricus gen. et sp. nov. is described from mid-Cretaceous amber of Myanmar based on examination of a single female specimen, and represents the unique taxon inclusion of fossils of the family Dytiscidae (Coleoptera: Adephaga) from Oriental Region. A new tribe, Ambraticini trib. nov. is established. The new taxon is assigned to subfamily Dytiscinae. This description represents one of a limited number of diving beetle taxa described from fossiliferous amber and is currently the oldest known fossil assigned to Dytiscinae. Key morphological characters of the new taxon are illustrated, and compared with tribes of Dytiscinae.